The Biophysical Modelling of the Equilibrium Receptors - Vincze, Janos; Vincze-Tiszay, Gabriella (British Journal of Healthcare and Medical Research, 2023)
The receiver or the analyser’s peripheral segment, the afferent pathway which takes the excitation to the cerebral cortex and the cortical segment. The simplest equilibrium takes place then two forces of equal size and directly opposed act simultaneously. If several forces act on different directions on an object, the object can be in equilibrium only if the effect of one is cancelled by the others. The equilibrium analyser is situated in the internal ear. The receptors of the macula are stimulated mechanically by the otolithes. Their stimulation takes place in static and dynamic conditions. This way, correcting motor reaction of the position of body and head are triggered at the level of the nervous centres, in order to maintain the equilibrium for the entire duration of movement. The vestibular sense is not a proper equilibrium sense, but an important component of the mechanisms which contribute to the adjustment of equilibrium, next to the kinaesthetic, visual, tactile analysers and cerebellum. The relative change of the stimulus is proportional with the relative change of the stimulus. They found that the so-called method of amplitude estimation resulted in values with very dispersed intervals, therefore, they applied the correlation of the analyzers.